Perancangan Antarmuka Pengguna Sistem Informasi Penjualan dan Inventori Barang pada Bagoplek menggunakan Goal-Directed Design - Erwin Wijayanto; Hanifah Muslimah Az-Zahra; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Nowadays, the development of technology has impacted business sector. Management information systems is highly needed for managing day-to-day business operation and websites used for increasing sales. Bagoplek has been running its day-to-day business manually, e.g. managing raw materials and ordering products. Therefore, several problems often appeared, such as: mismatched between the amount of stocks in the warehouse and delayed ordering the products due to the manual process. The aim of this research is to design an inventory information system to manage its stocks and design a website for online purchase so company could track the purchase record automatically. The methodology used in this study is the Goal-Directed Design. This method involves several processes, which are: gathering data of the potential users, describing business process models and system requirements specifications, creating a design framework. The result of this solution will be High-Fidelity Prototype design. The researcher will be using Usability Testing and System Usability Scale to test how user-friendly the solution design is and to measure usability based on acceptable score obtained by the solution design. The results contain several functional and non-functional inputs and the measurements' results using SUS got 69.13 for the inventory information system and 68.50 for the website, it shows that the design can be included in Marginal High and categorized as a good design.